Electronic Payment Method: Between the Inevitability of Banking Globalization and the Reality of the Monetary Function in Algeria - Abdeli, wafa (Journal of Legal Studies and Researches, 2017)
The market economy as an imposed option has made Algeria realize the need to modernize the payment system and introduce electronic payment methods that keep pace with the requirements of payment operations in electronic transactions to ensure speed and low costs in light of the disappearance of spatial and temporal boundaries, and the tangible progress of banking activity in light of the development of electronic communication networks, which has imposed the need to dedicate electronic payment methods, the most important of which are bank cards, as the most important monetary tool that ensures the development of the monetary function in Algeria.